Kritische Edition der Sahidischen Version des Johannesevangeliums: Text und Dokumentation - Foerster, Hans (2021)
Sahidic is the most important dialect of the Coptic language. Criticial editions of the Sahidic translation of the New Testament are a desideratum since many years. A research project (P29315) funded by the Austrian Science Fund (FWF) made the critical edition of the Sahidic Version of the Gospel of John possible. 172 different, mostly fragmentary manuscripts have been used for this edition.